Bovine herpesvirus 1 (BHV-1) infections in bovines: An economically important disease in India - Nandi, S; Yadav, Jeet Singh (Indian Farming, 2015)
Bovine herpesvirus-l (BHV-1) causes a variety of disease syndromes including, respiratory, nervous and reproductive disorders both in domestic as well as wild bovines that occur throughout the world including India. BHV-1 is a notifiable list B OIE disease. It causes severe economic losses due to weight loss, decrease in milk production and consequent restrictions in the international trade of livestock. In India, the disease is endemic and a number of outbreaks are reported every year from different states of the country. Although, vaccines are available against BHV-1 and routinely practiced in European countries, theimmunization in bovines is not carried out in India. The disease is not only be transmitted through aerosol but also through semen to the susceptible animals. Again, BHV- 1 infected cattle, once they recover from acute infection can prove very harmful to disease free herds because they are silent carriers of virus. Effective monitoring and control measures are required to avoid the risk of reintroducing BHV-1 into healthy herds/farms. Good farm management practices, zoo-sanitary and hygienic measures should also be adopted. OIE guidelines recommend 2-3 weeks quarantine period for newly introduced cattle after which only BHV-1 seronegative cattle are admitted to the herd. The help and co-operation from all the corners are needed to implement the control programme and successful eradication of the disease from the country.